The BLT Humanized Mouse Model as a Tool for Studying Human Gamma Delta T Cell-HIV Interactions In Vivo - Biradar, Shivkumar; Agarwal, Yash; Lotze, Michael T.; Bility, Moses T.; Mailliard, Robbie B. (Frontiers in Immunology, 2022)
Gamma-delta (γδ) T cells recognize antigens in a major histocompatibility complex (MHC) independent and have cytotoxic capability. Human immunodeficiency virus (HIV) infection reduces the proportion of the Vδ2 cell subset compared to the Vδ1 cell subset of γδ T cells in the blood in most infected individuals, except for elite controllers. The capacity of Vδ2 T cells to kill HIV-infected targets has been demonstrated in vitro, albeit in vivo confirmatory studies are lacking. Here, we provide the first characterization of γδ T cell-HIV interactions in bone marrow-liver-thymus (BLT) humanized mice and examined the immunotherapeutic potential of Vδ2 T cells in controlling HIV replication in vivo. We demonstrate a reduced proportion of Vδ2 T cells and an increased proportion of Vδ1 T cells in HIV-infected BLT humanized mice, like in HIV-positive individuals. HIV infection in BLT humanized mice also impaired the ex vivo expansion of Vδ2 T cells, like in HIV-positive individuals. Adoptive transfer of activated Vδ2 T cells did not control HIV replication during cell-associated HIV transmission in BLT humanized mice but instead exacerbated viremia, suggesting that Vδ2 T cells may serve as early targets for HIV replication. Our findings demonstrate that BLT humanized mice can model γδ T cell-HIV interactions in vivo.